An Unusual presentation of Bullous pemphigoid: A toxic epidermal necrolysis variant - Ravina Naik; Varadraj V Pai; Pankaj Shukla (Wolters Kluwer Medknow Publications, 2022)
Bullous pemphigoid (BP) is a subepidermal blistering skin disease that usually occurs in the elderly population. Morphological patterns of BP are varied and include lesions such as prurigo, urticaria, dyshidrosiform eczema, vegetative, erosive, erythema annulare centrifugum, nodular, and can very rarely toxic epidermal necrolysis. Drug-induced or drug triggered BP must be suspected if the disease subsides or remits on withdrawal of the probable offending drug. Dipeptidyl peptidase 4 inhibitors, aldosterone antagonists, anticholinergics, and dopaminergic medication are the common drugs associated with BP.